The rhabdoid variant of adrenocortical carcinoma-Report of three cases and literature review - Pavithra Ayyanar; Mukund N. Sable; Amit K. Adhya; Manoj K. Das; Madhabananda Kar; Pritinanda Mishra (Indian Journal of Pathology and Microbiology)
Adrenocortical carcinoma (ACC) is a rare and aggressive malignancy. Extensive rhabdoid morphology in ACC has been described recently in very few cases. The proportion of rhabdoid morphology and the role of SMARCB1/ INI1 expression in these tumor cells to diagnose the specific variant is not described in the literature. We reviewed the clinicopathological features of nine cases of adrenocortical neoplasm. Out of which, three cases of ACC showed predominant rhabdoid morphology. Large discohesive cells with abundant cytoplasm containing eosinophilic inclusions, eccentric vesicular nucleus, and prominent nucleoli. INI1 immunostain was retained in all cases. We reported the rhabdoid variant of ACC, a novel entity, and its diagnostic approach from their histological mimickers. Identifying more cases of this entity will help to clearly understand the pathogenesis, biologic behaviour, and any specific molecular alterations in the future.